Molecular features distinguish ten neuronal types in the mouse superficial superior colliculus. Issue 11 (26th January 2016) - Byun, Haewon; Kwon, Soohyun; Ahn, Hee‐Jeong; Liu, Hong; Forrest, Douglas; Demb, Jonathan B.; Kim, In‐Jung
Abstract : The superior colliculus (SC) is a midbrain center involved in controlling head and eye movements in response to inputs from multiple sensory modalities. Visual inputs arise from both the retina and visual cortex and converge onto the superficial layer of the SC (sSC). Neurons in the sSC send information to deeper layers of the SC and to thalamic nuclei that modulate visually guided behaviors. Presently, our understanding of sSC neurons is impeded by a lack of molecular markers that define specific cell types. To better understand the identity and organization of sSC neurons, we took a systematic approach to investigate gene expression within four molecular families: transcription factors, cell adhesion molecules, neuropeptides, and calcium binding proteins. Our analysis revealed 12 molecules with distinct expression patterns in mouse sSC: cadherin 7, contactin 3, netrin G2, cadherin 6, protocadherin 20, retinoid‐related orphan receptor β, brain‐specific homeobox/POU domain protein 3b, Ets variant gene 1, substance P, somatostatin, vasoactive intestinal polypeptide, and parvalbumin. Double labeling experiments, by either in situ hybridization or immunostaining, demonstrated that the 12 molecular markers collectively define 10 different sSC neuronal types. The characteristic positions of these cell types divide the sSC into four distinct layers. The 12 markers identified here will serve as valuable tools to examine molecular mechanisms that regulate development of sSC neuronal types. These markers could also be used to examine the connections between specific cell types that form retinocollicular, corticocollicular, or colliculothalamic pathways. J. Comp. Neurol. 524:2300–2321, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Using double labeling (either in situ hybridization or immunostaining), the authors discovered that the mouse superficial superior colliculus consists of at least 10 different neuronal types and four different layers. Each neuronal type or distinct layer has unique molecular features.